Die Anglo-Boereoorlog as stimulus vir die stigting van Afrikaanse plattelandse trustmaatskappye en eksekuteurskamers (Historia, 2021)
The gradual development of a common ethnic awareness among Afrikaans speakers after 1870 was accelerated by the Anglo-Boer War, and divided the inhabitants of the Cape Colony into loyalists and republican supporters. The heightened ethnic consciousness among pro-republican Afrikaans speakers manifested itself in the Cape Colony in a growing awareness, promotion and formulation of their interests on an ethnic basis. In the economic sphere Afrikaans speakers with republican sympathies withdrew their support from businesses which sympathized with the British war effort. The withdrawal of support from the loyalist controlled businesses underlined the lack of Afrikaner controlled alternatives. Against this background, and as a further manifestation of the Afrikaners' aspiration towards greater self-reliance in all business areas, initiatives were launched in 1900 in the Western Cape to further Afrikaner involvement in the field of trusts through the establishment of trust companies and boards of executors with a predominantly Afrikaans character and dedicated to the service of the Afrikaans community. Paarl African Trust Company Limited (PAT) and African Mutual Trust and Assurance Company Limited (AMT) materialized from these efforts.
Keywords: History; Ethnic economic awareness; Boland Bank; Board of Executors; African Mutual Trust and Assurance Company Limited; Anglo Boer War; Rural trust companies; Finance; Paarl African Trust Company Limited; Financial services conglomerates; Western Mutual Fire Assurance Company Limited